Acute Improvement in Intraoperative EMG During Common Fibular Nerve Decompression in Patients with Symptomatic Diabetic Sensorimotor Peripheral Neuropathy: EMG and Clinical Attribute Interrelations - Yamasaki, Dwayne S.; Nickerson, D. Scott; Anderson, James C. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Study Aims Electromyographic (EMG) recordings of the fibularis longus and tibialis anterior muscles were performed intraoperatively during nerve decompression (ND) of the common fibular nerve (CFN) in patients with symptomatic diabetic sensorimotor peripheral neuropathy. Patient demographics and clinical attributes were compared against changes in EMG after ND and analyzed for possible correlations.Methods Intraoperative changes in CFN EMG were analyzed for correlations against sex, age, body mass index (BMI), hemoglobin A1c (A1c), and type and duration of diabetes.Results Statistically significant changes were found between EMG changes and patient attributes, but no individual correlations were established. Significant EMG improvement was observed for both men and women (p < 0.0001 and p < 0.05, respectively), age groups (4th decade: p < 0.05; 5th decade: p < 0.05; 6th decade: p < 0.01; 7th decade: p < 0.005), diabetes duration (0–9 years: p = 0.002; 10–19 years: p = 0.002; 20–29 years: p = 0.03), and for type 1 and 2 diabetes (type 1: p < 0.005; type 2: p < 0.001). EMG improvement was greater in patients with the highest BMI levels (30–34.9: p = 0.014; 35–39.9: p = 0.013; > 39.9: p = 0.043), and highest A1c levels (> 6.4%; p < 0.0001).Conclusion Although long-term clinical studies are needed, these results provide insight into which patients might benefit most from this surgery. These results also suggest that surgical ND can produce an acute improvement in nerve function for both men and women, for people with type 1 and 2 diabetes, and across a wide range of ages, BMI, A1c levels, and disease duration.
Keywords: diabetic sensorimotor peripheral neuropathy; common peroneal nerve decompression; motor evoked potentials; acute objective functional improvement